Developing Packaging By Using Smart Material Which Helps to Realize Spoilage In Yoghurt - Eker, Bulent; Eker, Aysegul Akdogan (TRANS TECH PUBLICATIONS LTD, 2011)
The important effect of yoghurt on people's health caused increasing of many technological works and researches not only in our country but also all over the world. The environment in which yoghurt kept, may cause many sort of germs and contamination paths by the effects of some factors which are fairly similar to its own structure. These factors change the shelf-life of yoghurt and finally cause spoilage in yoghurt. In this context, it is known that the scientific works in this area which are aiming to minimize this spoilage effect, focus on the yogurt structure and packaging of yoghurt. The aim of this paper is to improve a smart polymer material which interacts with serum and changes color of the package by considering serum occurring within the shelf-life of yoghurt. PP based material will be used with the biological agencies like kaoline and talc and implemented mainly or superficial, the color change will be arised if the serum's PH increases. In practice, everyone can see the color changes with the window which will be placed on the label and the window will include the cautions according to the color levels.
Keywords: Smart; material; polypropilen; kaoline; pack; yoghurt; Materials Science